Principles of entrepreneurship (ENT530): Business model canvas: Calipar.co / Maria Maisarah Osman … [et al.] - Osman, Maria Maisarah; Erayu, Sharleyza; Ashak, Nur Azira; Mohd Kamal, Nurul Adira; Azman, Nurhafizatul Syafina (2020)
We have conducted SWOT analysis for our two competitors, Converse and Fippers. Converse is a long-running shoes product company while Fippers is a company that sells various design slippers. Both of these companies are well known and already have their own fans. Although these two companies already have loyal fans of their products, we find that there are still some weaknesses and threats in their business. However, it is common in a business where there will be strengths, weaknesses, opportunities and threats. Furthermore, under the element of key partnerships, Calipar.co has chosen Medshoe HQ as the supplier for shoes and slippers. We chose Medshoe HQ because it is one of the best shoes and slipper manufacturers in Malaysia. Calipar.co has also chosen to partner with Nova Infinity Sdn Bhd as our product packaging supplier. The design and price offered by Nova Infinity Sdn Bhd is very attractive and affordable. In addition, we chose J&T Express as the delivery service for our products to customers who purchase online. Thus, one of our key activities is our store operation at Mahkota Parade, Melaka. All our products located and sell at there and we also manage an online store. To variety our product, we also create and design new shoes. We market our product in social media to make sure our product and brand become well known in Malaysia. Additionally, under key resources we elaborate our financial sources which are consists of our own contribution, manpower plan and operational plan. As mentioned, our own contribution toward Calipar.co are RM100,000. Our company also rely to our administrative workers and suppliers. For value proposition, a great value proposition can help customers to fully understand the value of the company. By that, it helps to see what benefits them if we were able to be their choice in choosing the product. It is compulsory to understand customers’ problems in choosing materials and designing products because we want to maintain a good impression towards the customers. Next, customer relationship is good in maintaining loyalty and customer’s retention. It can enhance better service and could find new customers to purchase our product. It is a management strategy to increase the profits to our business by keeping in touch with the customers. By embracing social media is the best way to promote our business whether by making ads on Instagram or be on live on Facebook. Our customer segment is for young people and student in the range age of 15 to 24 years old. We decided to target customer that live near to the shop because it is preferable for customers that want to shop in-person to avoid barriers of miss communication happens. Other than that, some of our customer prefer to use the shoes for their academic session since the shoes give benefit to them to move fast. Calipar.co targeting a mass market as the product is unisex. Social media acts as the best platform to deliver products to customers. Right information from staff of Calipar.co is very important to the customer. By doing that, the customer will be clear with every information about the shoes they want to buy. So, there will no miss communications happened. Good communication will make customers feel comfortable and will make them interested in buying more often because the service provided to them is very good. Calipar.co spend RM35,000 for fixed assets which is for office equipment that we used in our business activity. Other than that, Calipar.co also used RM16,000 for marketing plan which is to advertise and promote our product using social media platform. Besides, to ensures efficient financial management to achieve our objectives, RM 10,000 was provided for Calipar.co as financial plan. In addition, RM25,000 are provided as operation cost for employees salaries, buying goods from suppliers and others. For revenue stream, our sales per day is RM9,480. We can sell our Shoesper around 120 units per day through websites and our physical store. Meanwhile, for sales per month would be RM9,480. After totalling up and making the calculation, our sales per year would be around RM1,769,760.